Planering av robotstall på Gästgivaregården Blacksta - Andersson, Andreas (SLU/Rural Buildings and Animal Husbandry (until 121231), 2010)
This work has been done to develop a plan for a future dairy barn at the Gästgivaregården and to show the space needed for cows and replacement heifers. It would also show the storage that will be needed. The design was largely based on results from studies on six different farms, but also the facts that are taken from research papers and articles in order to compare theory with practice. Because some farms only where interviewed by phone I have used a query form to obtain comparable resultes. The aim is to build a new barn with Automatic milking. I've drawn a milking stable for 120 milking cow and replacement heifers with the capability to house up to 140 milking cows if the farm would expand in the future. Calculations of feed amounts and space requirements have been made to see how many hectares are needed to supply the cows and replacement heifers with feed and to know about what size of storage space is required. The investigations made in this writing are to answer questions about the AMS-unit`s position and how to best maintain a good health status in the herd. It should also demonstrate how to plan when to have the young calfs in the same house. The drawing was designed to allow a good flow of livestock through the house without having to move animals for long distances, it should also be possible to make changes in the layout if it proves necessary in the future. The conclusion was that the position of the AMS-unit`s was not so important as long as the traffic around it was arranged. You should make sure that only those cows that have a milking permit hade access to the unit. The cows should be tempted to pass through the unit and not want to stay in the holding pen. The health status of the herd was related to how you maintain the AMS-unit. A unit that had been properly maintained should have a lower percent of interrupted milkings. Interrupted milkings leads to uneven milking intervals and that may increase the risk of milk leakage and contamination of other cows. Recruitment up to 6 months should be kept in a private area with its own ventilation to prevent air transmitted diseases to spread from the older animales. Allowing young animals go in the same system as the adults animals are preferable because they are learning how to function in that system.